2021
DOI: 10.1021/acs.iecr.1c01727
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Aging in Carbon Molecular Sieve Membranes Derived from PIM-1 and MOP-18

Abstract: Carbon molecular sieve membranes (CMSMs) commonly lose permeability over time due to the collapse of micropores. This decline in permeability, due to the densification of the membrane, is known as physical aging. CMSMs derived from polymers of intrinsic microporosity (PIM-1) are highly affected by physical aging, with declines in permeability greater than 60% over time. It is hypothesized that the densification of CMSMs derived from this high-free-volume polymer precursor is thermodynamically driven by the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
(101 reference statements)
0
17
0
Order By: Relevance
“…53 Metal–organic polyhedra (MOP) with long carbon chains attached to their outer shell are soluble in organic solvents and hence they can be utilized to disperse redox active metal nanoparticles. 54 Additionally, thermal decomposition of MOP structures creates porosity in the electrode enhancing the surface area and electrolyte accessibility after carbonization. Metal–organic polyhedra-18 (MOP-18) was used in this study as a PC precursor and to the best of our knowledge, this work presents the first hybrid supercapacitor based on a metal–organic polyhedra derived PC component.…”
Section: Introductionmentioning
confidence: 99%
“…53 Metal–organic polyhedra (MOP) with long carbon chains attached to their outer shell are soluble in organic solvents and hence they can be utilized to disperse redox active metal nanoparticles. 54 Additionally, thermal decomposition of MOP structures creates porosity in the electrode enhancing the surface area and electrolyte accessibility after carbonization. Metal–organic polyhedra-18 (MOP-18) was used in this study as a PC precursor and to the best of our knowledge, this work presents the first hybrid supercapacitor based on a metal–organic polyhedra derived PC component.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinking imparts polymer rigidity and plasticization-resistant properties with high permselectivity [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and reduction in physical aging [ 37 , 38 , 39 , 40 ] but is limited to the availability of functional groups in the precursor. Nakagawa et al reported the control of micropores via pillaring in a carbonized ion exchange resin [ 41 ], and, more recently, pillaring of CMSMs from the pyrolysis of MOP-18/PIM-1 mixed matrix membranes (MMMs) was reported by Cosey et al [ 42 ]. In this study, copper nanoparticles were created from the pyrolysis of the soluble copper-based metal–organic polyhedra (MOP-18, Figure 1 b) dispersed in PIM-1.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, incorporating nanoparticles into the polymer was found to be an efficient way to pillar the pore structure and thus prevent the collapse of molecular sieve membranes. 29 Inspired by this concept, UiO-66 nanoparticles were synthesized to serve as pillars to mitigate the aging of PIMs. To increase the compatibility between the MOF particles and PIM-1, defective engineering was adopted to allow the exposed −OH part in the carboxyl group of defective UiO-66 connecting with cyano groups and the carbonyl part in the carboxyl group with bare methyl groups of PIM-1 chains, as schematically shown in Scheme 1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Very recently, incorporating nanoparticles into the polymer was found to be an efficient way to pillar the pore structure and thus prevent the collapse of molecular sieve membranes . Inspired by this concept, UiO-66 nanoparticles were synthesized to serve as pillars to mitigate the aging of PIMs.…”
Section: Introductionmentioning
confidence: 99%